Adaptive Development of a Regional Spatial Data Infrastructure Facing Local Prospects and Socio-Technological Trends - Kalliola, Risto; Käyhkö, Niina; Jokela, Sanna (Bulletin of Geography. Socio-economic Series, 2019)
The regional Lounaispaikka-SDI (Spatial Data Infrastructure) in south-west Finland is being developed by a dynamic assembly of the region’s geospatial expertise and its networking, spatial data and geoportal services. Emerging as a data-centric constellation that supported the region’s geographical information professionals, this assembly has developed into a geospatial service with more broadly-focused public information on the region. This development has had five adaptive phases, each as a response to changing local needs and fast-evolving trends in information and communication technologies. Alongside these processes, the Lounaispaikka-SDI has also reinforced the region’s geospatial competencies with benefits offered to academia, public sector institutions, and companies.